2017
DOI: 10.1590/0104-1428.1959
|View full text |Cite
|
Sign up to set email alerts
|

Mixing process influence on thermal and rheological properties of NBR/SiO2 from rice husk ash

Abstract: ObstractSilica was extracted from rice husk ash (RHA) by a sequence of reactions to produce nanosilica. Two laboratory routes, co-coagulation and spray drying, were used to incorporate the nanosilica into the rubber matrix. Samples were characterized regarding filler incorporation efficiency, thermal stability, rheological behavior and morphology. Thermogravimetric analysis showed that spray-drying was the most efficient filler incorporation process and also the presence of silica increased the thermal resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the Table 2 it is shown that fusion temperatures of composite materials PP n RHA y PP n SBA remained in values of 147 °C; this in comparison with the two departure reprocessed materials of PP. The temperatures of initial degradation presente a more pronounced increase of PP n SBA, which it evinces the influence of ashes in absortion of the heat generated in the degradation processes, producing a deceleration of itself [22,23] . This behavior is also attributed to a set of characteristics produced by the presence of ashes in composite materials of the polymeric matrix, within them it is possible to find the effect that inorganic ashes have as nucleating agent, causing a foretaste in the beginning of crystallization of PP.…”
Section: Thermal Analysismentioning
confidence: 93%
“…In the Table 2 it is shown that fusion temperatures of composite materials PP n RHA y PP n SBA remained in values of 147 °C; this in comparison with the two departure reprocessed materials of PP. The temperatures of initial degradation presente a more pronounced increase of PP n SBA, which it evinces the influence of ashes in absortion of the heat generated in the degradation processes, producing a deceleration of itself [22,23] . This behavior is also attributed to a set of characteristics produced by the presence of ashes in composite materials of the polymeric matrix, within them it is possible to find the effect that inorganic ashes have as nucleating agent, causing a foretaste in the beginning of crystallization of PP.…”
Section: Thermal Analysismentioning
confidence: 93%
“…In order to provide technological application, depending on the application of the final product, the formulation of an elastomeric composition usually contain a filler, a curing system, processing and protecting agents such as antioxidants [3] . These components alter the compound viscosity with direct impact on processing as well as on the final product physical mechanical properties [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, rice husk contains about 20% of ash which can be recovered as amorphous silica [3]. Many types of research relating to extraction silica from rice husk and rice straw have been reported [4] [5] [6] [7] [8]. Della et al found the relative amount of silica was increased after burning out the carbonaceous material at different times and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Silica is one of the most important components and can be found in many applications such as biotechnology-related materials, medical-related materials [8], raw materials for cement industry [14]. Tailored materials composed of nanoparticles have potential for application in numerous technological fields [6].…”
Section: Introductionmentioning
confidence: 99%